2‐(1S)‐Camphanoyloxy‐2′‐phosphanylbiphenyl Ligands – Synthesis, Structure, and Preliminary Tests in Transition‐Metal Catalysis. Issue 20 (31st May 2017) - Wawrzyniak, Piotr; Kindermann, Markus K.; Thede, Gabriele; Thede, Richard; Jones, Peter G.; Enthaler, Stephan; Junge, Kathrin; Beller, Matthias; Heinicke, Joachim W.
Abstract : Diastereoisomer separation of the (1 S )‐camphanic acid 2‐isopropylphenylphosphanyl‐phenyl ester1 exemplifies the potential of (1 S )‐camphanoyl chloride for enantiomer separation of hydroxyl‐functional asymmetric phosphanes. Esterification of lithium 2′‐phosphanylbiphenyl‐2‐olates, generated from the respective 2‐OH or 2‐OSiMe3 precursors2aOH and2b –fSi, furnished the 2‐(1 S )‐camphanoyloxy‐biphenylphosphanes3a –c as 1:1 mixtures of diastereomers with low barriers for interconversion by rotation around the C–C axis (Δ G # = 70–73 kJ mol –1 for3a and3c by 31 P VT NMR spectroscopy). The P‐asymmetric compounds3d –f form 1:1 mixtures of stereoisomers. There is a tendency to cocrystallization of two preferred diastereoisomers, as shown by the crystal structure analyses of3dD and3fD, and in solution, there is a tendency toward partial isomerization to the sterically less‐favored atropisomers. The [RhCl(cod)(3dD )] complex4dD, however, seems stable in solution. Excess2dLi reacted with (1 S )‐camphanoyl chloride preferentially to form the ( S P, R ax, 1 S ) isomer, which was separated by crystallization as enantiopure3dE, characterized by single‐crystal XRD. Preliminary screening tests of this ligand in Rh‐catalyzed asymmetric hydrogenations of N ‐(1‐phenylvinyl)acetamide allowed high conversion and up to 59 % ee . Hydrosilylation of acetophenone proceeded with 78 % conversion and 48 % ee ; Suzuki–Miyaura couplings of 1‐bromo‐2‐naphthol with PhB(OH)2, in the presence of3b /[Pd(OAc)2 ], gave yields up to 98 %. Abstract : The potential of the (1 S )‐camphanoyl group for stereoisomer separation of asymmetric P, O hybrid ligands, successful for o ‐phosphanylphenyl ester, was tested for phosphanylbiphenyl‐2‐ols. The title compounds, structurally studied by solution NMR spectroscopy and single‐crystal XRD crystallography, tend to cocrystallization. Kinetically preferential ( S P, R ax, 1 S )‐3d was tested in catalytic reactions.